2016
DOI: 10.1001/journalofethics.2016.18.1.ecas2-1601
|View full text |Cite
|
Sign up to set email alerts
|

What's the Role of Autonomy in Patient- and Family-Centered Care When Patients and Family Members Don't Agree?

Abstract: ETHICS CASE What's the Role of Autonomy in Patient-and Family-Centered Care When Patients and Family Members Don't Agree? Commentary by Laura Sedig, MD Dave's health is on the decline. Despite surgery, chemotherapy, radiation, and hormonal treatments, his prostate cancer has metastasized to his bones. When he's been in and out of the hospital for four months or visiting clinic for lab tests and treatments, he's often accompanied by his wife Jessica and one or both of his two children, Christine and Alex. Dave'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Future physicians must learn and abide by these principles early in their career. (15)(16)(17)(18)(19) Several studies revealed that medical residents face many ethical challenges, sometimes on a daily basis, in addition to their negative attitudes and low level of knowledge. (20)(21)(22)(23)(24)(25)(26)(27)(28)(29) Therefore, the present study aimed to assess the baseline knowledge, attitudes and practices (KAPs) of medical residents in the Islamic Hospital in Amman (2017) towards healthcare ethics.…”
Section: Introductionmentioning
confidence: 99%
“…Future physicians must learn and abide by these principles early in their career. (15)(16)(17)(18)(19) Several studies revealed that medical residents face many ethical challenges, sometimes on a daily basis, in addition to their negative attitudes and low level of knowledge. (20)(21)(22)(23)(24)(25)(26)(27)(28)(29) Therefore, the present study aimed to assess the baseline knowledge, attitudes and practices (KAPs) of medical residents in the Islamic Hospital in Amman (2017) towards healthcare ethics.…”
Section: Introductionmentioning
confidence: 99%
“…Patients commonly consult their family members before they make decisions and consider the impact of their decisions on their families. Unfortunately, sometimes patients are coerced or threatened by family members and the patients lose their essential right of withholding their medical information [ 27 ]. Spouses may attempt to acquire information about each other for custody or divorce issues or a child may exploit the medical information to declare his parent as mentally incompetent for financial manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the presumption that the individualistic interpretation of patient autonomy reflects fundamentally from the Western value system is also not entirely correct. The modern Anglo-American push for self-determination only originated in the 1950s precisely because of the lack of self-determination that existed previously (prior to this era, patients in the USA had little autonomy over the treatments they received) and after the horrors recounted in the Nuremberg trials after World War II 2. Macklin notes that…”
Section: Comparing the East And West Using The Individualism-collecti...mentioning
confidence: 99%
“…Contemporary discussions regarding the patient-doctor relationship have repeatedly emphasised increasing standards for patient autonomy from a moralist, ethical and legal perspective, as seen through the Montgomery decision1 for informed consent in 2015. The current standard for patient autonomy seeks to enshrine the power of the patient vis-à-vis clinicians regarding decisions over their own care—that is, patients retain the fundamental decision-making power over their own care even if it contradicts professional medical judgement 2. Within this, privacy is seen as fundamental and a prerequisite for trust within the patient-doctor relationship, with modern ethical standards calling for physicians to protect patient privacy and confidentiality to the greatest extent possible 3–5…”
Section: Introductionmentioning
confidence: 99%